Consumption Pattern by Improving Blood Glucose Levels of Family Planning Acceptors of Injection Depo-Medroxy Progesterone Acetate - Ariesthi, Kadek Dwi; Pattypeilohy, Aning (KEMAS: Jurnal Kesehatan Masyarakat, 2020)
The most popular injection contraception in Kupang city is injection contraception. The use of injectable birth control, especially depo-medroxy progesterone acetate (DMPA) more than 4 times, will potentially increase weight. This weight gain, if not balanced with a healthy diet, will potentially increase blood glucose levels. The purpose of this study is to determine the relationship of consumption patterns with an increase in blood glucose levels in DMPA injection acceptor family planning in Kupang city. This study uses a cross-sectional design. 200 respondents selected using a purposive sampling technique with inclusion criteria have used DMPA injection family planning for more than 1 year and gained weight. Data collection uses a questionnaire and measurement of glucose levels uses auto-check. Data are analyzed bivariate and multivariate. The results of blood glucose level measurements showed that 32 (16%) of respondents have glucose levels above normal. The results of the analysis showed that the habit of consuming fatty foods significantly affected the increase in blood sugar of DMPA injection acceptor family planning.